Marketing Strategy of Love & Story Design - Šimůnková, Lucie; Král, Petr, 1979-; Zlatić, Marija; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
This diploma thesis deals with the creation of a marketing strategy for the Love & Story Design brand. The aim of this work was to evaluate the current strategy and improve it. The thesis is divided into two parts. The first part deals with the general marketing strategy for startups and their composition. In the second part of the thesis, a new strategy was set based on the data from the first and research in the form of qualitative and quantitative surveys.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses